Minimum wage non-compliance: The role of co-determination - Laszlo Goerke; Markus Pannenberg (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2023)
We analyse in what way co-determination affects non-compliance with the German minimum wage, which was introduced in 2015. The Works Constitution Act (WCA), the law regulating co-determination at the plant level, provides works councils with indirect means to ensure compliance with the statutory minimum wage. Based on this legal situation, our theoretical model predicts that non-compliance is less likely in co-determined firms because works councils enhance the enforcement of the law. The economic correlates of co-determination, such as higher productivity and wages, affect non-compliance in opposite directions. The empirical analysis, using data from the German Socio-economic Panel (SOEP) for the years 2016 and 2019, demonstrates that non-compliance occurs less often for employees in co-determined establishments, while there is no impact on the difference between the minimum wage and the amount, which was actually paid. Therefore, co-determination helps to secure the payment of minimum wages.
Keywords: J30; J53; K31; K42; M54; 330; Co-determination; Labour Law; Minimum Wages; Socio-Economic Panel (SOEP); Non-compliance; Works Councils